2022
DOI: 10.3390/ijerph19010585
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Climate Change and Variability on Estuarine Ecosystems: An Impact Study in Selected European, South American and Asian Countries

Abstract: It is well-known that climate change significantly impacts ecosystems (at the macro-level) and individual species (at the micro-level). Among the former, estuaries are the most vulnerable and affected ecosystems. However, despite the strong relations between climate change and estuaries, there is a gap in the literature regarding international studies across different regions investigating the impacts of climate change and variability on estuaries in different geographical zones. This paper addresses this need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 60 publications
0
9
0
1
Order By: Relevance
“…Among the environmental variables observed for the MES, the water temperature was strongly marked by seasonality. In this case, other atmospheric influences, such as precipitation, nearshore sea temperatures, and river run-offs, are likely to influence its variability (Leal Filho et al, 2022). High water temperature in the premonsoon was evident in the present study.…”
Section: Environmental Status Of Mahanadi Estuarymentioning
confidence: 51%
“…Among the environmental variables observed for the MES, the water temperature was strongly marked by seasonality. In this case, other atmospheric influences, such as precipitation, nearshore sea temperatures, and river run-offs, are likely to influence its variability (Leal Filho et al, 2022). High water temperature in the premonsoon was evident in the present study.…”
Section: Environmental Status Of Mahanadi Estuarymentioning
confidence: 51%
“…Even if long‐term environmental data series are needed to demonstrate that climate change could interfere with the eirenids‐bivalves relationship, we should increase our attention towards this association, above all in habitats prone to climate regime shifts, such as semi‐enclosed basins and estuarine habitats 88 . Monitoring activities will allow for prevention or control of eventual hydroid hyper‐proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Sharper differences occurred for both minimal values of SST and salinity between 1993-2010 and 2011-2020, which increased up to 5 C and 4 C, respectively. A new study on bivalve-inhabiting eirenids found in these basins could be useful to verify eventual changes in the distribution of the association and to detect areas that are more vulnerable to infestations.Even if long-term environmental data series are needed to demonstrate that climate change could interfere with the eirenids-bivalves relationship, we should increase our attention towards this association, above all in habitats prone to climate regime shifts, such as semi-enclosed basins and estuarine habitats 88. Monitoring activities will allow for prevention or control of eventual hydroid hyperproliferation.4 | CONCLUSIONSRegarding biotic/abiotic factors influencing the eirenids' prevalence and abundance, the proliferation of the polyp stage and the production of the free-living medusae/eumedusoids occur with high values of salinity; infestation occurs in sheltered and likely eutrophic areas with low water movement and low oxygen concentration.…”
mentioning
confidence: 99%
“…It is widely recognized that marine ecosystems are under threat (Consortium 2021). Ocean acidification, the global increase in sea surface temperature, and change in salinity along with overfishing, eutrophication, sedimentation, and pollution endanger marine species globally (Buck-Wiese, Voolstra & Brüwer 2016;Ducklow et al 2022;Leal Filho et al 2022). At the same time, marine organisms adjust and cope with changing environments (Fuhrman 2009;Reusch 2014;Foo & Byrne 2016;Abirami et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Ocean acidification, the global increase in sea surface temperature, and change in salinity along with overfishing, eutrophication, sedimentation, and pollution endanger marine species globally (Buck-Wiese, Voolstra & Brüwer 2016; Ducklow et al . 2022; Leal Filho et al . 2022).…”
Section: Introductionmentioning
confidence: 99%